2021
DOI: 10.1002/adfm.202009266
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Dynamics of Flexural Waves in Transformed Plates

Abstract: Coordinate‐transformation‐inspired optical devices have been mostly examined in the continuous‐wave regime: the performance of an invisibility cloak, which has been demonstrated for monochromatic excitation, is likely to deteriorate for short pulses. Here, pulse dynamics of flexural waves propagating in transformed plates is investigated. A practical realization of a waveshifter and a rotator for flexural waves based on the coordinate transformation method is proposed. Time‐resolved measurements reveal how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Moreover, Liu et al [348] experimentally demonstrated source illusion devices for flexural wave manipulation. Although not explicitly mentioned here, there is other notable research progress on the relevant topic [349][350][351][352][353][354][355][356][357][358].…”
Section: Othersmentioning
confidence: 99%
“…Moreover, Liu et al [348] experimentally demonstrated source illusion devices for flexural wave manipulation. Although not explicitly mentioned here, there is other notable research progress on the relevant topic [349][350][351][352][353][354][355][356][357][358].…”
Section: Othersmentioning
confidence: 99%
“…Further experiments by Misseroni et al [12,13] showed the possibility of cloaking flexural vibrations in structured plates. However, control of flexural pulse dynamics remains a further challenge [14,15]. We remark that most of the above literature concerns passive cloaking designs, since it exploits the concept of geometric transformation, in the tracks of what earlier proposed for electromagnetic waves.…”
Section: Introductionmentioning
confidence: 99%